Restorative Justice Education from Intrajudicial Criminal Mediation Associated Factors - Mercedes Matás Castillo; Inmaculada Méndez; Cecilia Ruiz Esteban; Gloria Soto (MDPI AG, 2021)
The restorative justice (RJ) paradigm requires coherence among legal, justice, and educational systems to promote a culture of restorative dialogue with victims of violence and to reintegrate aggressors into the community. The objective of this study, from an evolutionary social perspective, was to examine criminal mediation files in the archives of the Murcia Intrajudicial Criminal Mediation Service (UMIM), Spain, to see which variables are associated with which types of violence and understand the contents and adoption of agreements. In this study the sociodemographic, procedural, and interpersonal variables of 216 people who used criminal mediation were analysed. The results showed statistically significant differences concerning age, the procedural moment of referral, and the participants' relationship. The main conclusions are that the youngest group had a more significant number of encounters with physical violence; most agreements occurred in the initial phase of a judicial procedure; and the majority of agreements had moral content regardless of the age of the parties involved. These factors are of interest to the establishment of judicial and educational restorative models.